THE EFFECT OF PROBLEM BASED LEARNING (PBL) MODEL TO MATHEMATICAL COMMUNICATION SKILLS AND PROBLEM SOLVING 7 TH GRADE STUDENTS OF JUNIOR HIGH SCHOOL IN MERGANGSAN DISTRICTS OF YOGYAKARTA - Tiar Ayu Kuntari; Rosnawati Rosnawati (Jurnal Pedagogi Matematika, 2016)
AbstractThis  study  aims  to  determine  the  effect  of  problem  based  learning  models  for  mathematicalcommunication  and  problem  solving  skills  in  grade  VII  students  of  Junior  High  School  in districtMergangsan. The method in this study is a quasi experimental research with pre-test post-test groupdesign.  The  samples  in  this  study  are  the  students  of  Junior  High  School Taman  Dewasa  IbuPawiyatan of  grade  VIIA and  VIIB,  each  of  which  is  treated  with  problem-based  learning  andexpository model respctively. The instrument used in this study were the test and observation sheets.Data  analysis  technique  used were  T2-Hotteling  test  to  determine  the  significance  differences  andfurther  tests  using  independent  sample  t-test  test.  The  results  of   statistics  descriptive  test  analysisshowed  that  the  problem  based  learning  models  give  posttest  average  value  higher  than  theexpository, namely for the class with problem-based learning models have the posttest averaged valueof  84.25  for  mathematical  communication  skills  and  problem  solving  skills  of  85.05,.  While  in  theclassroom with expository have posttest average value of 71.64 and problem solving skills of 69.34.Based on the average results the model of problem-based learning is more influential and significantthan  the  expository  teaching  of  the  mathematical  communication  skills  and  problem  solving.Keywords: Problem Based Learning, mathematical communication, problem solving.